MANAJEMEN PENGEMBANGAN PENDIDIKAN KETERAMPILAN DALAM ISLAM - Fachruddin Azmi; Toni Nasution; Khairul Anwar; Muhammad Nasir (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2021)
Skills education is a necessity that must be owned by individuals in the era of globalization. This is because life skills are prioritized over knowledge, so an effective management and development system is needed. This paper aims to analyze the management of skills education development in Islam. This research uses a qualitative approach with a literature study method. Reference material is a tool for analyzing and testing the validity of the data. The results of this study indicate that the life skills needed by human resources are (1) general life skills (personal skills, rational thinking skills, social skills, and interpersonal skills) and (2) specific life skills (academic skills and vocational skills). Furthermore, efforts that must be made in developing skills education include reorienting learning, providing vocational skills and reforming educational institutions in terms of management and learning culture. Finally, extracurricular design as an effort to develop student skills education.